Cloud-Native Inventory Management System Using Flutter and Appwrite for Inventory Control - Muhammad Fajar; Azwar Azwar; Baharuddin Baharuddin (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Effective inventory management is crucial for retail operations like Toko Karya Rappang, an office stationery and printing business. The shop faces challenges in managing 163 active products due to manual logbook recording, which causes data errors, delayed stock monitoring, reporting difficulties, and late stock replenishment. This research designs a cloud-native mobile inventory management system using Flutter and Appwrite as Backend-as-a-Service (BaaS). Developed via the Rapid Application Development (RAD) method for speed and flexibility, the system supports two user roles (owner and staff). Key features include incoming/outgoing goods tracking, real-time stock monitoring, low-stock notifications, and visual sales reports. System evaluation utilized White Box, Black Box, and User Acceptance Testing (UAT). White Box testing yielded low Cyclomatic Complexity scores (3 to 5), indicating minimal logical risk. Furthermore, the UAT involving 10 respondents achieved an 86.17% feasibility score, placing it in the "Good" category. The system is proven to function effectively, enhance accuracy, improve inventory efficiency, and serve as a viable reference for small and medium retail businesses.